Legal strategies to stop violence to the tort of girls, boys and adolescents in their family environment. - Barletta Villarán, María Consuelo (2021)
This study brings us closer to the knowledge of legal strategies to stop violence against children and adolescents by members of the family group. For this purpose, a special protection with reinforced diligence is proposed for interventions in three cases: 1. Abuse in family dynamics under the power of parenting and discipline, which does not constitute a punishable act and is exercised by parents or legal representatives 2. Violence against girls, boys and adolescents by a member of their family environment that constitutes a crime and has a protective legal representative 3. Violence against children and adolescents by a member of their family environment that constitutes a crime and does not have a responsible protector. These intervention proposals are based on the recognition of two conditions that frame acts of violence in girls, boys and adolescents, the first referring to the risk situation of not having parental care and the second to the lack of family protection, both framed in Legislative Decree No. 1297 and its respective regulations. For the analysis of the aforementioned assumptions, three pertinent principles of the specialty are applied: The family as a fundamental institution for the development of people, the best interests of the child and due diligence.